New monodisperse magnetic polymer microspheres biofunctionalized for enzyme catalysis and bioaffinity separations - Horák, Daniel; Kučerová, Jana; Korecká, Lucie; Jankovičová, Barbora; Palarčík, Jiří; Mikulášek, Petr; Bílková, Zuzana (Macromolecular bioscience, 2012)
Magnetic macroporous PGMA and PHEMA microspheres containing carboxyl groups are synthesized by multi-step swelling and polymerization followed by precipitation of iron oxide inside the pores. The microspheres are characterized by SEM, IR spectroscopy, AAS, and zeta-potential measurements. Their functional groups enable bioactive ligands of various sizes and chemical structures to couple covalently. The applicability of these monodisperse magnetic microspheres in biospecific catalysis and bioaffinity separation is confirmed by coupling with the enzyme trypsin and huIgG. Trypsin-modified magnetic PGMA-COOH and PHEMA-COOH microspheres are investigated in terms of their enzyme activity, operational and storage stability. The presence of IgG molecules on microspheres is confirmed.
Keywords: Microscopy, Electron, Scanning; Magnets; imunoglobulin G; magnety; polymerizace; mikroskopie elektronová rastrovací; Spectrophotometry, Infrared; Ferric Compounds; trypsin; chromatografie afinitní; Immunoglobulin G; Trypsin; kyseliny polymethakrylové; železité sloučeniny; Humans; Microspheres; biokatalýza; Biocatalysis; imobilizované proteiny; Polyhydroxyethyl Methacrylate; polyhydroxyethylmethakrylát; spektrofotometrie infračervená; Immobilized Proteins; Chromatography, Affinity; mikrosféry; Polymethacrylic Acids; lidé; Polymerization